Responses of Active Ammonia Oxidizers and Nitrification Activity in Eutrophic Lake Sediments to Nitrogen and Temperature - Wu, Ling (Appl Environ Microbiol, 2019)
Ammonium concentrations and temperature drive the activities of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB), but their effects on these microbes in eutrophic freshwater sediments are unclear. In this study, surface sediments collected from areas of Taihu Lake (China) with different degrees of eutrophication were incubated under three levels of nitrogen input and temperature, and the autotrophic growth of ammonia oxidizers was assessed using (13)C-labeled DNA-based stable-isotope probing (SIP), while communities were characterized using MiSeq sequencing and phylogenetic analysis of 16S rRNA genes. Nitrification rates in sediment microcosms were positively correlated with nitrogen inputs, but there was no marked association with temperature. Incubation of SIP microcosms indicated that AOA and AOB amoA genes were labeled by (13)C at 20°C and 30°C in the slightly eutrophic sediment, and AOB amoA genes were labeled to a much greater extent than AOA amoA genes in the moderately eutrophic sediment after 56 days. Phylogenetic analysis of (13)C-labeled 16S rRNA genes revealed that the active AOA were mainly affiliated with the Nitrosopumilus cluster, with the Nitrososphaera cluster dominating in the slightly eutrophic sediment at 30°C with low ammonium input (1 mM). Active AOB communities were more sensitive to nitrogen input and temperature than were AOA communities, and they were exclusively dominated by the Nitrosomonas cluster, which tended to be associated with Nitrosomonadaceae-like lineages. Nitrosomonas sp. strain Is79A3 tended to dominate the moderately eutrophic sediment at 10°C with greater ammonium input (2.86 mM). The relative abundance responses of the major active communities to nitrogen input and temperature gradients varied, indicating niche differentiation and differences in the physiological metabolism of ammonia oxidizers that are yet to be described. IMPORTANCE Both archaea and bacteria contribute to ammonia oxidation, which plays a central role in the global cycling of nitrogen and is important for reducing eutrophication in freshwater environments. The abundance and activities of ammonia-oxidizing archaea and bacteria in eutrophic limnic sediments vary with different ammonium concentrations or with seasonal shifts, and how the two factors affect nitrification activity, microbial roles, and active groups in different eutrophic sediments is unclear. The significance of our research is in identifying the archaeal and bacterial responses to anthropogenic activity and climate change, which will greatly enhance our understanding of the physiological metabolic differences of ammonia oxidizers.